1995
DOI: 10.1002/app.1995.070561011
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and characterization of soluble polyimides

Abstract: SYNOPSISTwo kinds of soluble polyimides from pyromellitic dianhydride with Congo red and 4-sulfanilamide were prepared, respectively. Their structures were characterized by IR and 'H-NMR, and the thermal properties were investigated by DSC and TG-DTA. 0 1995 John Wiley & Sons, Inc.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
3
0

Year Published

1997
1997
2023
2023

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 6 publications
(1 reference statement)
0
3
0
Order By: Relevance
“…The mechanical properties of composite materials are directly determined by the interface between CF and the resin 3,15–17 . However, the solutions to interfacial bonding are different, depending on the characteristics of the resin 18–21 .…”
Section: Introductionmentioning
confidence: 99%
“…The mechanical properties of composite materials are directly determined by the interface between CF and the resin 3,15–17 . However, the solutions to interfacial bonding are different, depending on the characteristics of the resin 18–21 .…”
Section: Introductionmentioning
confidence: 99%
“…[2][3][4][5] In our earlier studies, we reported on the preparation and characterization of metal-containing polyureas 6 and bismaleimides 7 from divalent metal salts. We demonstrated that introducing metals into polyurea improved the thermal stability and the metal-containing bismaleimides had high thermooxidative stability and their temperatures of initial decomposition showed a relationship with metals introduced and imidization methods.…”
Section: Introductionmentioning
confidence: 99%
“…13 In the containing polymers. Some work about metal-conpresent work, a series of metal-containing bistaining polyimide [1][2][3] and polyurea, 4 in which new maleimides from divalent metal salts of p-aminoapproaches to metal-containing polymers were benzoic acid were prepared and characterized, first put forward, was carried out by us. Polymers and their thermal properties were also investifrom bismaleimides have been widely used due to gated.…”
Section: Introductionmentioning
confidence: 99%